Investigating Psychological Contract Breach and Perceived Betrayal on the Desire for Revenge and Avoidance among Customers of Luxury Hotels - Nasrin Rasouli; Saeid Farjam; Mahnaz Zabeh Ghazani; Somayeh Ghodrat (تحقیقات بازار یابی نوین, 2023)
Abstract The issue of the desire for revenge and avoidance of customers, caused by the feeling of perceived betrayal, is very important in service industries. Compared to hotels with stronger services, those with weaker services are more likely to suffer losses due to negative customer behavior. When customers receive services that are less than their expectations, the desire for revenge and avoidance is created. Thus, the present study aims to investigate the effects of the psychological contract breach and perceived betrayal on the desire for revenge and avoidance among customers of luxury hotels. This study is practical in purpose, correlational descriptive in nature, and survey-type in terms of the method of data collection. The statistical population was 331 customers of luxury hotels, who expressed their opinion through a ‘psychological contract breach’ questionnaire taken from Hai-Ming et al. (2020), ‘perceived betrayal, desire for revenge, and desire to avoid’ questionnaire taken from Rasouli et al. (2022). Structural equation modeling with SMART-PLS software was used to analyze the data. The findings show a significant effect of psychological contract breach on brand hatred. It was also shown that brand hatred has a positive and significant effect on the desire for revenge and avoidance. Consequently, focusing on creating and developing psychological contracts and avoiding betrayal, and being honest with customers can reduce the desire for revenge and retaliatory behaviors. Introduction Perceived betrayal is rooted in interactions between people and different organizations and businesses at various levels (GUNAWAN, 2018). When customers witness bad behaviors such as broken promises from businesses and organizations, they feel betrayed (Lee et al., 2020). When organizations and businesses fail to fulfill their promises and contracts, customers develop a negative attitude toward them. This feeling of betrayal is rooted in the expectations that customers have when interacting with organizations. People create expectations in their minds when interacting with organizations and businesses, and if the organization fails to meet these expectations, the customer may feel betrayed, which can lead to unfavorable results for the service provider organization (Hai-Ming et al., 2020).